GREEN GROWTH AND GREEN INFLATION-BASED MODEL IN 5G-20 COUNTRIES - Rosadi, Fachrial Djannah; Rusiadi, Rusiadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Promoting environmentally friendly economic growth, is practically crucial, as environmentally friendly economic growth and sustainable development complement each other. This research aims to build a panel model based on green growth and green inflation. The study uses secondary data with variables including green growth, green credit, green inflation, green bonds, green trade, macroprudential policies, green sustainable development, and green finance from January 2020 to December 2022. The objective is to develop prediction models using the Autoregressive Distributed Lag (ARDL) methodology. Panel ARDL combines autoregressive and distributed lag techniques, considering the time factor. The research findings reveal that overall, the leading indicator variable for green growth in the long run is green finance, while in the short run, there are two leading indicator variables: green finance and green inflation. Keywords: Green Inflation, Green Finance, Green Growth.